THE INFLUENCE OF CULTURAL TRADITIONS ON THE IMPLEMENTATION OF FAMILY RIGHTS IN KOSOVO AND METOHIJA (Heritage, 2025)
SummaryThis paper explores the influence of cultural traditions on the implementation of family rights in Kosovo and Metohija, with a special focus on the relationship between customary law and contemporary legislation. In the context of a multiethnic and post-conflict society, cultural norms play a significant role in shaping family relations, often influencing their legal regulation. This research points to the frequent conflict between cultural traditions and applicable legislation, particularly in the areas of marriage, divorce, guardianship and inheritance. The research is based on an analysis of customary law, which seeks to determine how cultural traditions shape legal reality and what challenges arise in harmonizing traditional values ​​with contemporary legislation.The aim of this paper is to examine how cultural traditions influence the realization of family rights in this region, with a focus on the challenges that arise in the application of the law in a multicultural and post-conflict context. The analysis is based on a multidisciplinary approach that includes empirical analysis, comparative law method, and theoretical insights from the fields of sociology and law.The results indicate the significant role of cultural traditions in shaping family relations, but also the need to improve legal awareness and harmonise customs and laws. The conclusion highlights recommendations for strengthening the legal protection of family rights through education, reforms and expanding dialogue between traditional communities and legal institutions.
Keywords: cultural traditions, family law, Kosovo and Metohija, customary law, women's rights, inheritance.